Simple Spectrofotometric Method For Detection Antioxidant Activity From Srikaya Leaves - Rifael Satrio Adinugroho; Anita Robiyatul Adawiyah; Winda Oktima (Journal Prima Health Science, 2019)
Several methods have been used for screening antioxidant activity,one of them is the DPPH method. 2,2-Diphenyl-1-picrylhydrazyl(DPPH) assay is the most commonly used antioxidant assay for plantextract. These assays can be time-consuming or require specializedequipment. The purpose of this research is to find out the antioxidantactivity using a spectrophotometer visible. Methanolic extract fromSrikaya (Annona squamosa L) leaves was obtained by the macerationprocess. Extract series was made at 100, 125, 150, 175, and 200(μg/mL) then reacted with 1 mL of DPPH (50 μg/mL). Afteroperating time in 30 minutes, measured the absorbance at 517 nm andantioxidant activity were calculated. The antioxidant activity can bemeasured simply using a spectrophotometer visible with DPPHreagent. From this reasearch, the maximum lamda is 517 nm. Themethanolic extract is strong with IC50 value of 99,20 μg/mL